(untitled) (Modern education and development, 2025)
Punctuation is a fundamental aspect of written language that ensures clarity, coherence, and proper meaning in communication. Understanding the rules and uses of punctuation marks helps writers structure their texts effectively, avoid ambiguity, and engage readers. This essay provides a detailed overview of punctuation types, their functions, common usage rules, and frequent errors to avoid.